Produção escrita : encontros e desencontros entre os livros didáticos de português do Brasil para estrangeiros e o exame CELPE-BRAS - Castro, Pedrina Barros de (2006)
Study of the writing production activities of didactic materials (DM) of Brazilian Portuguese for foreigners (BPF) Avenida Brasil (1 and 2) and Bem-Vindo! and writing production tasks of Celpe-Bras (Certificado de Proficiência em Língua Portuguesa para Estrangeiros) examination. Analysis of activities with investigation of their approach; analysis of the existence of links between writing and reading; and analysis of the contexts of use offered by the statements for textual production in the target language. Survey of the textual gender and functions presented and requested by the activities. Comparison of the writing production activities of the analyzed DMs of BPF to those of the Celpe-Bras tasks, searching for convergences and divergences, and verifying if the former can provide the teachers of BPF with an appropriate support to the development, in a communicative perspective, of foreign students writing abilities, who are usually candidates for Celpe-Bras. Conclusion indicating more divergences than convergences between the writing production activities of the analyzed DMs and Celpe-Bras writing production tasks, and demonstrating that the analyzed DMs do not offer support for the development of the abilities related to writing in accordance with the presuppositions of the examination.